Photocatalysis of Cr- and Fe-Doped CeO2 Nanoparticles to Selective Oxidation of 5-Hydroxymethylfurfural - Jeong-Woo Nam; Vy Ngoc Pham; Jeong Min Ha; Minjeong Shin; Hangil Lee; Young-Sang Youn (Nanomaterials, 2022)
Oxygen vacancies (Vo) present in CeO2 nanoparticles (NPs) can effectively boost their photocatalytic activity under ultraviolet (UV) light. To improve photocatalytic performance, Cr- and Fe-doped CeO2 NPs with increased Vo were prepared using a simple method of doping Cr and Fe ions into CeO2 NPs, which was confirmed by an in-depth analysis of the structural and electronic changes. Through photocatalytic degradation (PCD) experiments with 5-hydroxymethylfurfural (HMF), we found that the PCD rates of the two doped CeO2 NPs were faster than that of the CeO2 NPs. In addition, the conversion of HMF to 2,5-furandicarboxylic acid (FDCA) using the doped CeO2 NPs occurred only through the mechanism of the selective oxidation to 5-hydroxymethyl-2-furancarboxylic acid (HMFCA), exhibiting better efficiency than using CeO2 NPs.